Ethyl [1-(4-bromophenyl)-1-hydroxy-3-oxobutyl](phenyl)phosphinate monohydrate - Samanta, S.; Perera, S.; Broker, G.A.; Zhao, C.G.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title hydrate, C18H20BrO4P center dot H2O, a staggered conformation is found when the organic molecule is viewed down the central P-C bond, with the oxo and hydroxyl groups being diagonally opposite; each of the central P and C atoms has an S-configuration. The crystal structure features supramolecular double chains along the b axis mediated by O-hydroxyl-H center dot center dot center dot O-oxo, Owater-H center dot center dot center dot O-oxo, and O-water-H center dot center dot center dot O-water hydrogen bonds.